Sinking dynamics of particulate matter in the subarctic and subtropical regions of the western North Pacific. (February 2019) - Sukigara, Chiho; Mino, Yoshihisa; Kawakami, Hajime; Honda, Makio C.; Fujiki, Tetsuichi; Matsumoto, Kazuhiko; Wakita, Masahide; Saino, Toshiro
Abstract: Sinking particles collected by drifting sediment traps at 100 and 200 m depths at two observation sites, K2 and S1, located in the subarctic and subtropical gyres in the western North Pacific, respectively, were fractionated in 5 ranges of sinking velocities between 5 and 1000 m d −1 using an elutriation system. The velocity distributions were divided into two distinct types over both sites: type-S containing more particles at the relatively slow end of the velocity range and type-F including a peak in the middle range (50–150 m d −1 ). These distributions showed little change between 100 and 200 m, although fluxes of particulate organic carbon (POC) decreased vertically. The averaged sinking velocities ( w poc ) calculated from the velocity distributions of POC were 31 ± 16 and 63 ± 26 m d −1 at K2 and S1, respectively. For S1 particles, a positive correlation was found between w poc and content of CaCO3 . This result indicates that particles containing large amounts of denser CaCO3 sink faster than those containing large amounts of organic matter with low densities. Particles at K2, which were mainly composed of opal and organic matter, did not exhibit a clear relationship between w poc and the content of denser opal. Instead of opal, w poc had a positive correlation with δ 15 N of the sinking particles and was small (large) when the surface layer was stratified (well-mixed). The attenuation of POC flux with depth resulted from physical fragmentation of particles by turbulence at K2 and from biological decomposition and fragmentation at S1. Highlights: Sinking velocity of particulate matter measurement by an elutriation system. Particles containing large amount of CaCO3 sink faster. Particles in the subarctic region sink faster in the well-mixed season.